EFFICACY OF FIXED COMBINATION OF VALSARTAN, AMLODIPINE AND HYDROCHLOROTHIAZIDE IN COMPLEX THERAPY OF THE PATIENT OF VERY HIGH CARDIOVASCULAR RISK - I. M. Sokolov; N. A. Zheleznyakova (Столичная издательская компания, 2015)
The high prevalence of arterial hypertension in association with high and very high cardiovascular risk requires widespread use of combined therapy. Current approaches to selection of combination components of antihypertensive drugs are based the efficacy of these drugs proven in multicenter randomized clinical trials. The triple combination of calcium antagonist, angiotensin II receptor blocker and thiazide diuretic is regarded as the best option for combined therapy in patients with arterial hypertension and ischemic heart disease to reduce cardiovascular risk.